Analysis of cable force on steady-state motion of remotely operated vehicle for reaction pool underwater welding. (21st June 2019) - Li, Zhan-Dong; Tao, Jian-Guo; Sun, Hao; Li, Jing-Kui; Luo, Yang; Deng, Zong-Quan
Remotely operated vehicle is a reliable and efficient tool in routing inspection of reactor pools of nuclear power plants. While, there is still no study on steady-state motion of remotely operated vehicle which is crucial for reaction pool underwater welding reported. In practice, the cable force has been considered as a critical factor affecting the vehicle's operation. To evaluate and predict the disturbing effect caused by the cable mounted on the tailing of a vehicle, a numerical simulation can be employed. In this work, we set up a theoretical model of a cable partially in reaction pool water and air to validate the remotely operated vehicle design and reduce the prototype developing time. We programmed the model governed by an ordinary differential equation set, which was considered as an initial value problem following a dimensionless treatment to be solved. The influence by factors (i.e. velocity, water depth, entry water angle, water density and cable length on tension, normal shear force, and binormal moment) was quantified by a numerical method. The test of a cable force was carried out to verify an authenticity of the three-dimensional mechanical model and a numerical method. The results demonstrated that the presented method could be used to evaluate the effect of real environment factors on a remotely operated vehicle steady-state motion and held a potential to improve the remotely operated vehicle design and control strategy.